Develoment Automated Rice Packaging Via Embedded System - ศิริมาศเกษม, ธัญภพ; ขวัญวงษ์, กฤษติยพงษ์; แสงโชติ, อิษฎา; แก่นสม, ศักดิ์ศรี; ตั้งจิตเจริญเลิศ, ธเนศ; ศรีคุณ, อิสรี; วรเนตรสุทธิกุล, กวีพจน์; แก่นสม, ปาริฉัตร; สัตถาผล, ประชารัฐ (Journal of Energy and Environment Technology of Graduate School Siam Technology College, 2017)
The purpose of the development of automatic rice packaging system with embedded system to learning, design, creation, and testing for system performance. Microcontroller model ATMEGA328P is used as a receiver and controller. The monitor was done on screen with 4 lines of 20 alphabets and select buttons. The pneumatic system is used for folding the two ends of the bag together. Heating from the coil is used for sealing three remaining sides of the bag and use the DC motor to move the packaging. The performance of rice packing machine is derived from error of 10 times weighing and operation of the packaging system. The weight testing is divided into 3 ranges: 500 grams and 1,000 grams. The results when loading 500 grams, 700 grams and 1,000 grams of rice found that error value was 3.7%, 2.6%, and 1.7% respectively. Rice was not leaked out from the bag and cutting system can be off completely every time. According to the above test results, it can be concluded that the performance of automatic rice packaging machine can work very well and meet to the purpose.